Reconstructing Professional Identity: A Phenomenological Study of Teacher Certification and 21st-Century Learning - Siti Rahma Sari; Hasan Hariri; Riswandi Riswandi; Atik Rusdiani; Suddin Lada (Jurnal Pendidikan Progresif, 2026)
This study evaluates the implementation of teacher certification policies from the perspectives of professionalism and 21st-century learning performance. Rather than evaluating policy effectiveness through measurable outcomes, this phenomenological study investigates how certified teachers perceive, interpret, and experience the certification policy in their daily professional lives, revealing its implications for teacher professionalism and 21st-century learning performance. Data were collected through in-depth interviews with seven certified teachers from diverse educational backgrounds. The data highlight three interconnected themes that reflect teachers’ lived experiences with certification. First, the reconstruction of professional identity examines how certification alters teachers’ self-perceptions, increasing their feelings of legitimacy, moral responsibility, and commitment to ongoing professional development. Second, the disparity between certification policy and pedagogical practice illustrates teachers’ perspectives of a disconnect between the administrative and compliance-oriented nature of certification procedure and the limited support for meaningful classroom innovation. Third, adaptive challenges in 21st-century learning transformation highlight teachers’ struggles to translate certification outcomes into student-centered, digitally integrated, and competency-based instruction, often stemming from insufficient post-certification mentoring and inconsistent digital preparation.  Findings indicate that while certification enhances teachers’ professional recognition and self-efficacy, it remains limited in fostering authentic pedagogical innovation. The study concludes that certification should be reconceptualized as a dynamic, continuous process that integrates mentoring, reflective practice, and digital pedagogy. This study specifically recommends integrating post-certification mentoring focused on reflective classroom practice, including formative assessments of 21st-century pedagogical competencies in certification frameworks, and establishing school-based professional learning communities to bridge the gap between policy expectations and teachers’ lived classroom realities. Keywords: teacher certification, teacher professionalism, 21st-century learning, phenomenology, professional development.